SPE Middle East Unconventional Resources Conference and Exhibition 2015
DOI: 10.2118/172947-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Identification and Comprehensive Evaluation of the Parameters by Dual Laterolog Data

Abstract: Quality and productivity of tight formations are heavily dependent on the degree of fracture development. In fact, hard and dense carbonate formations may not be considered as net pay without presence of fractures which conduct fluids towards wellbore. The evaluation of fractures is a key to reservoir effectiveness characterization for well drilling, completion, development and simulation of fractured reservoirs. Although new imaging technologies such as Formation Micro-Scanners and Imagers (FMS and FMI) provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, the appearance for closed or filled fractures is resistive if the filling materials are dense like calcite or anhydrite. In some cases, full set logs such as PEF, RHOZ, resistivity logs and NPHI are very useful for such kind of differentiation (Saboorian-Jooybari et al 2015;Tokhmchi et al 2010). It is noteworthy that fracture aperture is only measurable using some electrical imaging tools (not all image logs) for open fractures.…”
Section: Natural Fracture Analysis and Fracture Aperture Using Electrmentioning
confidence: 99%
“…However, the appearance for closed or filled fractures is resistive if the filling materials are dense like calcite or anhydrite. In some cases, full set logs such as PEF, RHOZ, resistivity logs and NPHI are very useful for such kind of differentiation (Saboorian-Jooybari et al 2015;Tokhmchi et al 2010). It is noteworthy that fracture aperture is only measurable using some electrical imaging tools (not all image logs) for open fractures.…”
Section: Natural Fracture Analysis and Fracture Aperture Using Electrmentioning
confidence: 99%
“…The largest of FBRs in Vietnam is Bach Ho located in Cuu Long Basin [3]. Many studies have conducted overviews of geological and production characteristics for FBRs [4,5]. These studies have shown that FBRs have low matrix porosity and permeability and that fluids are mainly stored and flow in natural fractures.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that the sonic transit times are affected by reservoir properties that include compaction, porosity, anisotropy, density, lithology, cementation, consolidation, overburden stress and pore pressure (Khazanehdari and Mccann 2005;Krief et al 1990;Thomsen 1986;Toksöz et al 1976;Williams 1990). A good understanding of how these properties change over the life of the reservoir is essential for proper reservoir planning, development and management (Dakhelpour-Ghoveifel et al 2019;Khazanehdari and Mccann 2005;Saboorian-Jooybari et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Well-calibrated and reliable sonic logging tools are necessary to acquire accurate measurements of compressional and shear wave transit time, otherwise, the formation evaluations and estimation become false and misleading (Onalo et al 2018a. Typical anomalies observed in well logs have been presented in the literature (Saboorian-Jooybari et al 2016. This may result in the development of non-potential reservoirs and the abandonment of potential reservoir formations.…”
Section: Introductionmentioning
confidence: 99%